The relevance of rich club regions for functional outcome post‐stroke is enhanced in women. Issue 4 (28th November 2022) - Bonkhoff, Anna K.; Schirmer, Markus D.; Bretzner, Martin; Hong, Sungmin; Regenhardt, Robert W.; Donahue, Kathleen L.; Nardin, Marco J.; Dalca, Adrian V.; Giese, Anne‐Katrin; Etherton, Mark R.; Hancock, Brandon L.; Mocking, Steven J. T.; et al.
Abstract: This study aimed to investigate the influence of stroke lesions in predefined highly interconnected (rich‐club) brain regions on functional outcome post‐stroke, determine their spatial specificity and explore the effects of biological sex on their relevance. We analyzed MRI data recorded at index stroke and 3‐months modified Rankin Scale (mRS) data from patients with acute ischemic stroke enrolled in the multisite MRI‐GENIE study. Spatially normalized structural stroke lesions were parcellated into 108 atlas‐defined bilateral (sub)cortical brain regions. Unfavorable outcome (mRS > 2) was modeled in a Bayesian logistic regression framework. Effects of individual brain regions were captured as two compound effects for (i) six bilateral rich club and (ii) all further non‐rich club regions. In spatial specificity analyses, we randomized the split into "rich club" and "non‐rich club" regions and compared the effect of the actual rich club regions to the distribution of effects from 1000 combinations of six random regions. In sex‐specific analyses, we introduced an additional hierarchical level in our model structure to compare male and female‐specific rich club effects. A total of 822 patients (age: 64.7[15.0], 39% women) were analyzed. Rich club regions had substantial relevance in explaining unfavorable functional outcome (mean of posterior distribution: 0.08, area under the curve: 0.8). In particular, the rich club‐combination had a higher relevance than 98.4% of random constellations. Rich club regions were substantially more important in explaining long‐term outcome in women than in men. All in all, lesions in rich club regions were associated with increased odds of unfavorable outcome. These effects were spatially specific and more pronounced in women. Abstract : Lesions in rich club regions were associated with increased odds of unfavorable outcome. These effects were spatially specific, that is, the majority of random combinations of six regions had comparably smaller effects on long‐term outcome. Effects were substantially more pronounced in women.